Comparative study of graft materials used in myringoplasty - Gupta, Anchal; Gupta, Apurab; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Various graft materials are used for myringoplasty in practice. Present study was done to compare the hearing improvement and graft uptake rate in patients with inactive mucosal type chronic otitis media with central perforation undergoing myringoplasty using either of the two graft materials: temporalis fascia and conchal perichondrium. Methods: Patients with tubotympanic type of chronic suppurative otitis media were selected from patients attending the ENT OPD of SMGS Hospital, Government Medical College, Jammu between July 2016 to March 2018. This study included 100 patients out of which 50 were subjected to myringoplasty with temporalis fascia grafting (Group 1) and remaining 50 to conchal perichondrium grafting (Group 2) using underlay technique. The comparative study was done on following parameters-graft uptake and audiological outcome. Results: 82% patients were of age less than 30 years. The overall male: female ratio was 1.3:1. In Group 1, 76% had gain of 15 db while 12% had gain of >15 db. In Group 2, 72% had gain of 15 db and 8% had gain of >15 db. The graft was intact in 84% patients. 12% of Group 1 patients, showed residual perforation whereas it was 20% in Group 2 patients. Conclusions: The study showed that: the temporalis fascia graft is better than conchal perichondrial graft for closure of perforations in inactive mucosal type of chronic otitis media with central perforation because of maximum hearing improvement and minimal failure rate in group receiving temporalis fascia graft.